Bleeding Risk Assessment in Patients with Venous Thromboembolism - Nopp, Stephan; Ay, Cihan (Hämostaseologie, 2021)
The recommended treatment for patients with venous thromboembolism (VTE) is anticoagulation for at least 3 months. However, anticoagulant treatment increases the risk of bleeding, and patients at high risk for major bleeding might benefit from treatment discontinuation. In this review, we discuss strategies for assessing bleeding risk and compare different bleeding risk tools. Bleeding risk assessment is best viewed as a continuous approach with varying challenges throughout the acute and chronic phase. At diagnosis, bleeding risk factors must be identified and reversible risk factors treated or modified. After initial treatment, repeated bleeding risk assessment is crucial for the decision on extended/long-term anticoagulation. Current clinical prediction models (e.g., HAS-BLED, RIETE, or VTE-BLEED scores) are externally validated tools with relevant differences in specificity and sensitivity, which can aid in clinical decision-making. Unfortunately, none of the current bleeding risk assessment tools has been investigated in clinical trials and provides evidence to withhold anticoagulation treatment based on the score. Nevertheless, the HAS-BLED or RIETE score can be used to identify patients at high risk for major bleeding during the initial treatment phase, while the VTE-BLEED score might be used to identify patients at low risk for bleeding and, therefore, to safely administer extended/long-term anticoagulation for secondary thromboprophylaxis. As clinical prediction scores still lack predictive value, future research should focus on developing biomarker-based risk assessment models.
Keywords: venous thromboembolism; anticoagulants; risk assessment; hemorrhage